The Features of Management of Innovation Risks at Pre-investment Stage of the Project in Modern Economic Realities - Zozulya, Valentina; Romanchenko, Olga; Zuykov, Andrey; Zozulya, Inga (International Review of Management and Marketing, 2017)
The research deals with conceptual and methodological problems of investment project management including the questions of innovation risks or in other words risks of innovations at different stages of the project but mainly in respect of pre-investment stage. No doubt, one of these problems is organization or conceptual architecture of such projects, which can in general depend on the processes exactly at pre-investment stage. It’s clearly known - most investment initiatives were failed because of key weaknesses just when project had been in the form of idea. That’s why it’s extremely significant to form proper mechanisms or models which can let interested participants to determine the risks and influence of different factors both on the results of innovations and execution quality of investment projects and programs. Taking into account the specifics of investment project management and different methodologies of project organization in different industries, using methods of analogy and stage case-analysis, conditions the author’s «Model of investment project effectiveness assessment and management of innovation risks» was developed and represented in this scientific work. This model is especially usable for construction industry. We can certainly say that the effectiveness of investment projects can depend on the combination of some indicators such as net present value (NPV), lifecycle of the project, the number, quality and dynamic of movable and immovable fixed assets changes, innovation and other types of risks at different project stages and the methodology of project organization. Keywords: innovation risks, investment project, methods of modelling JEL Classifications: M11, M21